The Relationship Between Fluid Intake Restrictions and Hemodialysis Adequacy for Chronic Renal Failure Patients During Hemodialysis Treatment In Hemodialysis Unit at Dr. Slamet District General Hospital - Engkus Kusnadi; Siti Ratnasari Wulan (STIKes Karsa Husada Garut, 2015)
Restriction of fluid intake is a factor of the hemodialysis adequacy, which is very important in the hemodialysis success therapy for patients with chronic renal failure. The purpose of this study was to assess the relationship between fluid intake restriction and hemodialysis adequacy for chronic renal failure patients during hemodialysis therapy. This study used descriptive correlational design. The independent variable was fluid intake restriction and the dependent variable was the hemodialysis adequacy. The sample in this study was 52 patients with chronic renal failure during hemodialysis therapy in hemodialysis units dr.Slamet Garut Hospital. The result showed that most of patient (73.1%) had appropriate fluid restriction. Out of this number, 78.9% was adequate and 21.9% was inadequate. The rest (26.9%) was inappropriate fluid restriction. Out of this number, 42.9% was adequate and 57.1% was inadequate. The contingenci coefesien test showed p.value = 0.012 which was less than α (0.05). Thus, H0 was rejected and it can be concluded that there was a significant relationship between fluid intake restriction and hemodialysis adequacy. For nurses in Hemodialysis Unit dr. Slamet Garut, the result can be used to promote health education using banner as a media, so that the patients and families can enhance their attention about fluid intake that consumed by the patient.